Ladakh's artificial glaciers: climate-adaptive design for water scarcity. (29th July 2017) - Clouse, Carey; Anderson, Naomi; Shippling, Taylor
Abstract : For decades, the artificial glaciers in Ladakh, North India, have been trumpeted as useful water-harvesting devices for subsistence farming communities. In this context, the massive masonry structures link low-tech, vernacular hydrological thinking with design innovation to create a popular climate-adaptive design solution. While these interventions appear to provide promising new strategies for water harvesting in this dry desert region, very little data exist to substantiate, quantify, or contradict the project claims. This paper interrogates these structures through the lens of the design disciplines and considers the functional aspects of a prototypical artificial glacier system. Six different artificial glacier systems were studied over a period of two summer months, revealing a variety of design and construction approaches. These findings give rise to a number of engineering patterns that may be found in an archetypical artificial glacier system.